Relative deprivation, personal income satisfaction, and average well-being under different income distributions - Christian Seidl; Stefan Traub; Andrea Morone (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper uses the data gained from an income categorization experiment for five shapes of income distributions to investigate background context effects, relative deprivation, range-frequency theory to explain background context effects, individual income satisfaction versus aggregate well-being, and the dual patterns of income categorization and limen setting. It is shown that background context effects exist and are reflected in relative deprivation. Not all precepts of range-frequency theory can be evidenced. Moreover, we demonstrate a welfare paradox which concerns a contradiction between individual income satisfaction and aggregate well-being. Finally, income categorization and limen setting harbor no response-mode effects, but exhibit conformity.
Keywords: D31; D63; C91; 330; relative deprivation; income distributions; income satisfaction; context effects; Einkommensverteilung; Disparitätsmaß; Verteilungsgerechtigkeit; Lebensstandard; Test; Theorie; Meinung